2018
DOI: 10.1002/hed.25484
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of postoperative complications after total thyroidectomy with Graves' disease

Abstract: Background The effect of Graves' disease on the risk of postoperative complications in patients undergoing total thyroidectomy is unclear. Methods The incidence of recurrent laryngeal nerve (RLN) injury and hypoparathyroidism were analyzed between 165 patients with Graves' disease (GD group) and 1:1 matched patients with euthyroid states (control group). Results The matched cohorts did not differ in age, sex, body mass index, pathologic diagnosis, and extent of operation. Excised thyroid weight was higher in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The a priori exclusion of thyroid reoperation and surgery for malignant disease excluded these factors from the present analysis. As already described by other authors 17,18 , the present study has confirmed that thyroiditis increases the rate of postoperative VCP. In contrast, for permanent VCP, thyroiditis is debatable as a risk factor based on the theoretical models calculated for the present cohort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The a priori exclusion of thyroid reoperation and surgery for malignant disease excluded these factors from the present analysis. As already described by other authors 17,18 , the present study has confirmed that thyroiditis increases the rate of postoperative VCP. In contrast, for permanent VCP, thyroiditis is debatable as a risk factor based on the theoretical models calculated for the present cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from IONM, factors influencing postoperative VCP rates are thyroiditis (Graves' disease or Hashimoto's thyroiditis) 17,18 and malignancy 1,19 . Especially in thyroid malignancy, deliberate resection of the RLN for oncological reasons is inevitably associated with permanent VCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parathyroid glands play significant roles in maintaining a good balance between serum calcium and phosphorus, but are vulnerable to be injured during surgical operation because of their small volumes and variable locations. Temporary hypoparathyroidism [1,2] was seen in more than 30% of patients undergoing total thyroidectomy, --and the incidence of permanent hypoparathyroidism (hypoparathyroidism lasting for over 6 postoperative months) was [3,4] up to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The major complication of thyroid resection for GD is postoperative hypoparathyroidism with transient and permanent rates between 18.0-20.0% and 3.0-7.0% [14][15][16][17], followed by postoperative bleeding and recurrent laryngeal nerve palsy (RLNP). The underlying causes are complex.…”
Section: Introductionmentioning
confidence: 99%